2020
DOI: 10.3390/jmse8100792
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Diversity of Two Marine Gobies (Gobiiformes: Gobiidae) from the North-Eastern Atlantic and the Mediterranean Sea

Abstract: Gobies (Gobiiformes: Gobiidae) are the most species-rich family of fishes in general, and the most abundant fish group in the European seas. Nonetheless, our knowledge on many aspects of their biology, including the population genetic diversity, is poor. Although barriers to gene flow are less apparent in the marine environment, the ocean is not a continuous habitat, as has been shown by studies on population genetics of various marine biota. For the first time, European marine goby species which cannot be col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…The concatenation of the COI and 16S rRNA genes that was used in the present study has also proved useful and more informative in other genetic studies of bivalves ( Yuan, He & Huang, 2009 ; Feng et al, 2011 ; Slynko et al, 2018 ), and shows that there is a certain level of differentiation between the P. nobilis populations in the Western vs Eastern Basin. Consistently with the Mediterranean pattern of diffusion already proposed in Sanna et al (2013) for this species, this finding suggests that the already known oceanographic barriers at the Sicily Strait and at the Otranto Strait might be limiting the dispersal of the species and minimizing the gene flow ( Čekovská et al, 2020 ). Due to its short pelagic larval duration stage, P. nobilis is a species which is considered to be rather affected by currents and fronts; at the same time, it could be less prone to gene flow from other locations ( Pascual et al, 2017 ) and it could exhibit strong population structuring, as has been shown for other bivalves also characterized by a short planktonic larval stage ( Ye, Wu & Li, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…The concatenation of the COI and 16S rRNA genes that was used in the present study has also proved useful and more informative in other genetic studies of bivalves ( Yuan, He & Huang, 2009 ; Feng et al, 2011 ; Slynko et al, 2018 ), and shows that there is a certain level of differentiation between the P. nobilis populations in the Western vs Eastern Basin. Consistently with the Mediterranean pattern of diffusion already proposed in Sanna et al (2013) for this species, this finding suggests that the already known oceanographic barriers at the Sicily Strait and at the Otranto Strait might be limiting the dispersal of the species and minimizing the gene flow ( Čekovská et al, 2020 ). Due to its short pelagic larval duration stage, P. nobilis is a species which is considered to be rather affected by currents and fronts; at the same time, it could be less prone to gene flow from other locations ( Pascual et al, 2017 ) and it could exhibit strong population structuring, as has been shown for other bivalves also characterized by a short planktonic larval stage ( Ye, Wu & Li, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…The maximum intraspecific distance was especially high in Z. pallaoroi sp. nov. (over 5%), as well as M. macrocephalus (3.8%), compared to Z. zebrus and European marine gobies from the Gobiuslineage, where values range between 1 and 2.2% Čekovská et al, 2020;Z. zebrus in this work).…”
Section: Discussionmentioning
confidence: 48%
“…However, our study found that the genetic variations of nuDNA were lower than that of mtDNA in T. bifasciatus (Table 1 and Figures 1B, 4). Moreover, our study found that the four-eyed sleeper, Bostrychus sinensis, on the Pacific coastline of China (Qiu et al, 2016), two marine gobies, Gobius geniporus and Gobius cruentatus, from the north-eastern Atlantic and the Mediterranean Sea (Cekovská et al, 2020), and bifurcate mussel, Mytilisepta virgata, in northwestern Pacific coastline (Lee et al, 2021) all displayed the same pattern. The genetic variations of nuDNA, Ryr3, the first intron of ribosomal protein gene S7, and ITS1, were lower than those of mtDNA.…”
Section: Discordance Between Mitochondrial and Nuclear Markerssupporting
confidence: 51%